39 SUPPLEMENTAL VITAMIN A NORMALIZES MESSENGER RIBONUCLEIC ACID LEVELS OF STAT3 AND E-CADHERIN IN PRETERM LAMBS TREATED WITH CONVENTIONAL VENTILATON. (1st January 2006) - Au, K.; McKnight, R. A.; Dahl, M. J.; Hale, M.; Callaway, C.; Fu, Q.; Yu, X.; Lane, R. H.; Albertine, K. H.
Abstract : Background: Conventional ventilation (CV) impairs alveolar formation in preterm humans and lambs, whereas nCPAP preserves alveolar formation. 2D protein electrophoresis identified STAT3, a transcriptional factor regulating cell proliferation, and E-cadherin, a cell adhesion molecule, as candidate genes affected by CV. Vitamin A (VitA) supplementation of CV-treated preterm lambs normalizes alveolar formation. Objective: We hypothesized that VitA of the CV-treated preterm lamb would normalize mRNA levels of STAT3 and E-cadherin. Methods: Preterm lambs were treated with CV or nCPAP. Half of the CV lambs were treated with 5, 000 U/kg/d of VitA. Ovine STAT3 and E-cadherin cDNAs were cloned and sequenced. Lung mRNA levels of STAT3 and E-cadherin in 3 d preterm lambs treated with CV ( n = 3), CV + Vit ( n = 4), nCPAP ( n = 4), as well as term lamb lungs ( n = 4). Results: The STAT3 sequence was 631 bp and demonstrated 94% homology to human STAT3. The E-cadherin sequence was 818 bp and demonstrated 83% homology to human E-cadherin. The following results are presented as percent of nCPAP ± SEM. VitA decreased STAT3 and E-cadherin mRNA levels to 52 ± 14% ( p < .05) and 62 ± 15% (p = .09) of nCPAP levels respectively. No significant differences in lung mRNA levels existed for the 2 genes between CV + VitA and normal term lambs. Conclusion: VitA supplementation normalizes mRNA levels of STAT3 and E-cadherin toward the levels found in normal term lambs, which may represent a VitA-induced maturational effect. Supported by CHRC, HL62875, HL56401, T35 HL07744.